Hunger in war and peace: an analysis of the nutritional status of women and children in Germany, 1914-1924 - Cox, M; Mary Cox (2015)
The question posed by this dissertation is very simple. What was the nutritional status of women and children in Germany during and subsequent to the First World War? The question itself is an old one, but it continues to be argued. To approach this issue, I have placed it in the context of a few of the century-old debates, continuing still, that relate to what the Germans called the 'Hungerblockade'. At the outbreak of the First World War England initiated a naval blockade against Germany that would last through the cessation of hostilities and through Armistice until after the signing of the Treaty of Versailles, in July, 1919. Since that time, scholars have debated the legality of this interdiction. International law at the time was a bit unclear as the Treaty of London, designed in part to secure the trading rights of neutral countries during warfare, was signed by ten nations, including England, but never ratified. Hence, the legal status of the blockade is still questioned. Interestingly, questions on the legality of the blockade have related to the treatment of neutral countries, rather than to the harming of German civilians. Beyond the legality of the blockade, historians and ethicists have also questioned its morality. Perhaps the blockade was technically legal, but was it moral to deliberately harm noncombatants? Recently, the famous historian of the First World War, Jay Winter, has even gone so far as to declare that the British blockade against Germany "did not fall short of being a war crime". And yet, other serious historians argue that Germany did not experience great deprivation during the period of blockade. Some even call reports of blockade-induced hunger in Germany, among women and children, a "myth". Obviously, siege warfare has been practiced for centuries. And in many ways, one could argue that a blockade allows time for an enemy to consider its options and surrender if necessary, rather than continue to live under the blockade or siege. I believe that none of these debates would interest historians nearly so much if the blockade had not effectively reduced the living standards of civilians. The ethics of the blockade would not matter nearly so much if Germans and others did not claim that hunger was wielded as a weapon of war against innocent non-combatants. This dissertation, therefore, is an analysis of the living standards of women and children in Germany from 1914–1924, but the materials I employ to answer it include, in addition to a small portion of the vast literature mentioned earlier, international law, treaties, old household surveys by German doctors, anthropometric studies on the weights and heights of school children, fishing maps, letters, annual reports and internal documents aid agencies, and children’s drawings. Using these materials may seem rather eclectic for an historian, but together they make a narrative that is both persuasive, and compelling. Women and children did, indeed, suffer nutritional deprivation during and following the War. For children, this deprivation varied a great deal depending on who their parents were. If parents were of high enough status or wealth to send their child to one of the elite schools, they were also, at least during the War, more capable of mitigating the nutritional deficiencies in the legal market food supply during the War. Children in the poorer strata of society, those more vulnerable to the pernicious impact of poverty, had few options to offset the reduced food supply. Often mothers would sacrifice for their children, and yet even their sacrifices were ultimately limited—there is a limit to how much a mother can reduce her own caloric intake before she suffers from chronic energy deficiency, is forced to lead a sedentary existence, or dies. I also analyze living standards of the well to do and poorer children in Germany during the period of Armistice, which lasted for eight months, and even after the blockade had been lifted, when there were still millions of children in Germany who were underfed, hungry, and suffering from malnutrition. The plight of children in Germany after the war was answered by thousands of people from around the world. From many nations, they responded by donating time, material goods, or money for their relief. These were massive, trans-global efforts, because many people believed that German children and their mothers needed help. I consider the charitable practices of a few of the major aid givers including the American Friend Service Committee, various aid practices in Switzerland, and the Save the Children Fund of Britain. I present not only statistics about their operations, but consider the best practices they adopted to efficiently deliver needed nourishment to German children. I show that all three of these aid agencies independently determined to help the most needy children in Germany first. This helps explain why after the War, German children from poor families had marked improvement in their nutritional statuses, while those in the higher echelons of society continued to plateau for several years longer. Finally, I conclude this dissertation by analyzing unpublished children's drawings and letters to determine how international aid was received, interpreted, and imagined by German children. These drawings and letters document the process of triage and strengthen the argument that aid was a significant factor in the rapid recovery of the poorer children in the population.